Evaluation of the agronomic and economic performances of integrated rice-fish systems in Mali - Akpoffo, Marius; Guindo, Jonathan; Dossou-Yovo, Elliott (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Agriculture, livestock, and fisheries are central to Mali’s economy, yet the country faces growing challenges from climate change, land degradation, and water scarcity, threatening food security and livelihoods. This study evaluated the agronomic and economic performance of integrated rice-fish systems as a climate-smart agriculture innovation promoted under the AICCRA project in Mali. Field experiments were conducted across three sites (Baguineda, Selingue, and Massala) using six treatments: rice monoculture without fertilizer (T1), fish monoculture (T2), rice monoculture with fertilizer (T3), rice irrigated with fish pond water (T4), integrated rice-fish with fish in the middle (T5), and integrated rice-fish with fish at the border (T6). Results showed that rice yield, fish yield, rice equivalent yield, system productivity efficiency, gross revenue, and net benefit were significantly influenced by both site and farming system. Baguineda consistently outperformed the other sites across all parameters, while Massala recorded the lowest performance. Among treatments, T5 (Rice-Fish middle) consistently produced the highest system productivity efficiency and net benefit, outperforming even T3 (Rice with recommended fertilizer) by increasing productivity efficiency by 0.15 t/ha/day and net benefit by USD 11,251/ha while maintaining comparable rice yields. These findings highlight the potential of integrated rice-fish systems, particularly rice-fish with fish pond in the middle of rice field, as a viable strategy for improving farm productivity and income while reducing reliance on chemical fertilizers in Mali’s rice-based systems.